Composition for forming precursor film, composite, and method for producing composite

A composition-based surface treatment method using an organometallic compound and ultraviolet light effectively addresses the safety and scalability issues of existing methods, achieving strong and stable bonding of difficult-to-adhesive resins.

JP2025055843APending Publication Date: 2025-04-08NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023165234
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing surface treatment methods for difficult-to-adhesive resins, such as those using sodium metal or plasma treatments, pose safety risks, environmental concerns, and limitations in scalability and long-term bonding stability.

Method used

A composition comprising an organometallic compound, a surfactant, and a solvent is used to form a precursor film on a difficult-to-adhesive resin substrate, which is then treated with ultraviolet light to convert the film into an inorganic metal film, activating the surface for improved bonding.

Benefits of technology

This method enables stable and safe bonding of difficult-to-adhesive resins in open air conditions, with enhanced bonding strength and long-term surface treatment effectiveness, suitable for applications like high-frequency electric circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025055843000005
    Figure 2025055843000005
  • Figure 2025055843000006
    Figure 2025055843000006
  • Figure 2025055843000007
    Figure 2025055843000007
Patent Text Reader

Abstract

To provide a composition for forming a precursor film which is used to enhance the bondability of low-adhesion resin surfaces and can be used stably and safely in an open atmosphere; a composite; and a method for producing the composite.SOLUTION: A composition for forming a precursor film comprises an organometallic compound, a surfactant, and a solvent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a precursor film-forming composition, a composite, and a method for producing the composite. [Background technology]

[0002] For the production and processing of poorly adhesive resins such as fluororesins, a surface treatment technique is required to make the surface of the poorly adhesive resin easier to bond by chemical and physical treatment. Conventionally, the surface treatment technique involves impregnating the resin surface with a reagent in which metallic sodium is dispersed, and activating the surface by chemical treatment (see, for example, Patent Document 1).

[0003] Recently, as the surface treatment technology, a physical treatment method that does not use a reagent has been implemented, in which the surface is treated by plasma treatment or corona discharge treatment in which nitrogen, hydrogen, or the like is introduced as a process gas, and functional groups are formed by a reaction between the process gas and the resin, thereby activating the surface (see, for example, Patent Documents 2 and 3). Also, instead of a treatment for making the surface of a poorly adhesive resin easier to bond, a method has been reported in which a poorly adhesive resin is fused by locally irradiating a laser onto the contact interface with a different material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-201571 A [Patent Document 2] Japanese Patent Application Publication No. 7-164600 [Patent Document 3] JP 2016-56363 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the chemical surface treatment method using metallic sodium in Patent Document 1 uses a highly reactive and unstable reagent in the atmosphere, which poses problems of high danger to workers and a large environmental burden during storage, use, and disposal of the reagent. In addition, there are problems with the appearance of the resin turning black due to the excessive reaction of the reagent, and sodium penetrates into the resin and remains even after cleaning, affecting the resin performance.

[0006] The surface treatments using corona discharge and plasma treatments described in Patent Documents 2 and 3 were developed to solve these problems, but they require treatment equipment with atmospheric control and vacuum exhaust mechanisms, making it difficult to treat large areas. In addition, there are problems in that the activated state of the surface often does not last for a long time, making it necessary to perform bonding immediately after treatment.

[0007] The fusion method using laser heating has the advantage that no prior surface treatment is required, but it has the problem that it requires high-power density laser irradiation during bonding and can only be applied to bonding between materials that have a large difference in absorbance of laser light. In addition, deformation occurs during thermal welding, making it difficult to apply to thin sheet-like resins in particular, and the interface is prone to unevenness due to deformation, making it unsuitable for high-frequency electrical circuit boards that require high smoothness.

[0008] The present invention has been made in consideration of the above circumstances, and aims to provide a precursor film-forming composition, a composite, and a method for producing the composite, which are used to make the surface of a poorly adhesive resin easier to bond and can be used stably and safely in an open atmosphere. [Means for solving the problem]

[0009] The present invention has the following aspects. [1] A precursor film-forming composition comprising an organometallic compound, a surfactant, and a solvent. [2] The precursor film-forming composition according to [1], wherein the organometallic compound is a metal organic acid salt or a metal alkoxide. [3] The precursor film-forming composition according to [2], wherein the organometallic compound is a compound that exhibits absorption of ultraviolet light having a wavelength of 100 nm or more and 400 nm or less. [4] The precursor film forming composition according to [2] or [3], wherein the organometallic compound contains, as a metal ion, one or more metal elements selected from the group consisting of first transition metal elements Sc, Ti, V, Cr, Mn, Fe, Co, Ni, and Cu, and Group 1 elements Li, Na, and K. [5] The composition for forming a precursor film according to any one of [1] to [4], wherein the surfactant is added in order to apply a solution of the composition for forming a precursor film to a poorly adhesive resin. [6] The precursor film-forming composition according to any one of [1] to [5], wherein the solvent is capable of dissolving the organometallic compound and the surfactant. [7] A substrate made of a poorly adhesive resin and an active surface formed on the surface of the substrate, The active surface has a carbon-fluorine (CF) bond of the base material partially substituted with a carbon-oxygen (CO) bond, A complex, in which a ratio of the content of the carbon-oxygen (CO) bonds to the total amount of the carbon-fluorine (CF) bonds and the carbon-oxygen (CO) bonds (CO bonds / (CF bonds+CO bonds)×100(%)) is 30% or more. [8] The complex according to [7], wherein the arithmetic mean roughness (Ra value) of the surface (3 μm square) of the active surface is 20 nm or less. [9] An inorganic metal film is formed on the substrate via the active surface, The composite according to [7] or [8], wherein the inorganic metal film contains a metal ion compound derived from an organometallic compound.

[10] The composite according to [9], wherein the inorganic metal film is bonded to the substrate via the active surface with a bonding strength of 7 N / mm or more.

[11] The composite according to [9] or

[10] , wherein the inorganic metal film has a surface (3 μm square) having an arithmetic mean roughness (Ra value) of 20 nm or less.

[12] The composite according to any one of [7] to

[11] , wherein the poorly adhesive resin is a fluororesin.

[13] A first step of applying the precursor film-forming composition according to claim 1 onto a substrate made of a poorly adhesive resin to form a coating film on the substrate; a second step of drying the coating to remove the solvent and form a precursor film containing the organometallic compound; and a third step of irradiating the surface of the precursor film with ultraviolet light to remove organic components from the precursor film and convert the precursor film into an inorganic metal film, and activating the surface of the base material by catalytic activity of components in the inorganic metal film to form an active surface on the surface of the base material.

[14] A method for producing the composite according to

[13] , comprising a fourth step of removing the inorganic metal film by dissolving it with water or a weak acid to expose the active surface on the surface of the substrate. Effect of the Invention

[0010] According to the present invention, it is possible to provide a precursor film-forming composition, a composite, and a method for producing a composite, which are used to make the surface of a poorly adhesive resin easier to bond and can be used stably and safely in an open atmosphere. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a cross-sectional view showing a composite body according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a composite body according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a diagram showing the results of elemental analysis by X-ray photoelectron spectroscopy for the substrates of Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 4] FIG. 2 is a diagram showing the results of elemental analysis by X-ray photoelectron spectroscopy for the substrates of Examples 1 and 2 and Comparative Examples 1 and 2. [Diagram 5] FIG. 2 is a diagram showing the results of elemental analysis by X-ray photoelectron spectroscopy for the substrates of Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 6] FIG. 2 is a diagram showing the results of elemental analysis by X-ray photoelectron spectroscopy for the substrates of Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 7] FIG. 2 is a diagram showing the results of elemental analysis by X-ray photoelectron spectroscopy for the substrates of Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 8] FIG. 2 is a diagram showing the mechanism of formation of an active surface, which is presumed from the results of elemental analysis by X-ray photoelectron spectroscopy, for the substrates of Examples 1 and 2 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] An embodiment of the precursor film-forming composition, the composite, and the method for producing the composite of the present invention will be described. It should be noted that the present embodiment is specifically described to allow a better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified.

[0013] [Precursor film forming composition] A precursor film-forming composition according to one embodiment of the present invention contains an organometallic compound, a surfactant, and a solvent.

[0014] "Organometallic compounds" The organometallic compound is selected from a metal organic acid salt or a metal alkoxide, and the metal ion species is at least one of a transition metal ion and an alkali metal ion. The organometallic compound is preferably a compound that exhibits absorption of ultraviolet light having a wavelength of 100 nm or more and 400 nm or less. Examples of transition metal ions include first transition metal elements such as scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), and copper (Cu). Transition metal ions have high absorption and catalytic functions for ultraviolet light. Examples of the alkali metal ion compound include Group 1 elements such as lithium (Li), sodium (Na), and potassium (K). Alkali metal ions have a strong bond to fluorine. These compounds may be used alone or in combination of two or more. The organometallic compound is preferably, for example, a compound consisting of these metal ions and at least one selected from a carboxyl group having 1 to 4 carbon atoms (CH3COO-, C2H5COO-, C3H7COO-, C4H9COO-) and a carbonyl group, or a β-diketonate or a long-chain alkoxide having 6 or more carbon atoms. Specific examples include 2-ethylhexanoate of sodium (Na) or nickel (Ni).

[0015] The content of the organometallic compound in the precursor film-forming composition of this embodiment is preferably 0.1% by mass to 10% by mass, more preferably 0.5% by mass to 5% by mass, based on the total mass (100% by mass) of the precursor film-forming composition. If the content of the organometallic compound is less than the lower limit, it becomes difficult to cover the entire surface of the resin substrate with an inorganic metal film. If the content of the organometallic compound exceeds the upper limit, the thickness of the precursor increases, and the irradiated light does not reach the surface of the substrate, making it difficult to form an active surface.

[0016] "Surfactants" The surfactant is used to coat the solution of the precursor film-forming composition on the substrate made of a poorly adhesive resin with good wettability, and is selected according to the substrate to be coated. If the coating can be performed with good wettability without a surfactant, the surfactant is not necessarily required. Examples of the surfactant include fluorine-based surfactants, hydrocarbon-based surfactants, and silicone-based surfactants. Fluorine-based surfactants and hydrocarbon-based surfactants that do not contain inorganic metal components that are not decomposed by light irradiation and leave residues are more preferred.

[0017] The content of the surfactant in the precursor film-forming composition of this embodiment is preferably 5% by mass or less, more preferably 0.5% by mass or less, based on the total mass (100% by mass) of the precursor film-forming composition. The smaller the surfactant content, the more preferable it is, as long as sufficient wettability is obtained for forming a precursor film on a substrate, and if coating with good wettability is possible without a surfactant, the surfactant may not be contained. If the surfactant content exceeds the upper limit, it may not be removed by the reaction due to light irradiation and may remain as a residue in the inorganic metal film.

[0018] "solvent" The solvent is not particularly limited as long as it can dissolve the organometallic compound and the metal ion compound. Examples of such solvents include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, styrene, and pyridine, and alcohols such as 1-butanol, isopropanol, ethanol, methanol, ethylene glycol, and normal propyl alcohol. These solvents may be used alone or in combination of two or more. The aromatic hydrocarbon is preferably toluene or xylene from the viewpoints of solubility of the organometallic compound, adjustment of viscosity, and wettability to the substrate. Many organometallic compounds are sold diluted in toluene or xylene solvents, making them easy to use.

[0019] The content of the solvent in the precursor film-forming composition of this embodiment is preferably 80% by mass or more and 99.9% by mass or less, more preferably 95% by mass or more and 99.5% by mass or less, based on the total mass (100% by mass) of the precursor film-forming composition. If the content of the solvent is less than the lower limit, the viscosity increases, making it difficult to apply a uniform thin film, and making it difficult to form the precursor film. If the content of the solvent exceeds the upper limit, the amount of effective ingredients for forming the precursor film decreases, making it difficult to form the precursor film.

[0020] The precursor film-forming composition of this embodiment can be used stably and safely, and therefore the surface of the substrate can be locally modified only in the desired area by limiting the application area using various printing techniques or limiting the irradiation area of ​​ultraviolet light using a photomask or the like.

[0021] [Complex] A composite according to one embodiment of the present invention has a substrate made of a poorly adhesive resin and an active surface formed on the surface of the substrate.

[0022] FIG. 1 is a cross-sectional view showing a composite body according to one embodiment of the present invention. As shown in FIG. 1, the composite 1 of the present embodiment has a substrate 2 made of a poorly adhesive resin, an active surface 3 formed on a surface 2a of the substrate 2, and an inorganic metal film 4 formed on the substrate 2 via the active surface 3.

[0023] "Base material" The substrate 2 is made of a poorly adhesive fluororesin. Examples of poorly adhesive fluororesins include polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and tetrafluoroethylene-ethylene copolymer (ETFE).

[0024] The thickness and shape of the substrate 2 are not particularly limited.

[0025] "Active surface" The active surface 3 is a surface formed by using the precursor film-forming composition of the above-mentioned embodiment and by the manufacturing method described below. In the active surface 3, some of the carbon-fluorine (CF) bonds of the substrate 2 are replaced with carbon-oxygen (CO) bonds, and the ratio of the carbon-oxygen (CO) bond content to the total content of carbon-fluorine (CF) bonds and carbon-oxygen (CO) bonds (CO bonds / (CF bonds+CO bonds)×100(%)) is 30% or more, and preferably 50% or more. If the ratio (CO bonds / CF bonds) is less than the lower limit, sufficient bonding strength to the inorganic metal film 4 is not exhibited.

[0026] The active surface 3 is formed when the organometallic component in the precursor film reacts with the carbon-fluorine (C-F) bonds that constitute the surface 2a of the substrate 2 when exposed to irradiated light, removing fluorine (F) from the substrate 2 and exchanging it with oxygen (O), thereby replacing some of the carbon-fluorine (C-F) bonds with carbon-oxygen (C-O) bonds.

[0027] "Inorganic metal film" The inorganic metal film 4 is a layer formed by using the precursor film forming composition of the above embodiment and by the manufacturing method described below. The inorganic metal film 4 contains metal ion compounds derived from the organometallic compound and oxygen derived from the atmosphere or fluorine derived from the resin. It is formed when the organic components of the organometallic compound in the precursor film are decomposed and volatilized by light irradiation, resulting in inorganic matter. The anion components of the metal ion compounds in the inorganic metal film are mainly composed of oxide ions, although they are affected by the organometallic compound and the atmosphere during light irradiation.

[0028] The thickness of the inorganic metal film 4 is not particularly limited, but is preferably, for example, 5 nm or more and 100 nm or less.

[0029] The arithmetic mean roughness (Ra value) of the surface 4a (3 μm square) of the inorganic metal film 4 is preferably 20 nm or less, more preferably 10 nm or less. If the arithmetic mean roughness (Ra value) of the surface 4a (3 μm square) of the inorganic metal film 4 exceeds the upper limit, when the film is used as a high-frequency communication circuit board of 100 GHz or more, the transmission loss caused by the unevenness of the surface 2a of the base material 2 increases, impairing the performance of the circuit.

[0030] The arithmetic mean roughness (Ra value) of the surface 4a (3 μm square) of the inorganic metal film 4 can be measured by a stylus scanning method or the like based on the Japanese Industrial Standard JIS R 1683:2014.

[0031] According to the composite 1 of the present embodiment, the surface 2a of the substrate 2 has an inorganic metal film 4 made of an easily adhesive inorganic material, and therefore the adhesiveness of the surface 2a of the substrate 2 is excellent. Furthermore, according to the composite 1 of the present embodiment, the inorganic metal film 4 covering the surface 2a of the substrate 2 functions as a protective layer, and therefore the effect of the surface treatment can be maintained for a long period of time. Furthermore, by selecting an organometallic compound, it is possible to simultaneously impart a function such as electrical conductivity to the inorganic metal film 4 covering the surface 2a of the substrate 2.

[0032] [Method of manufacturing the composite] A method for producing a composite according to one embodiment of the present invention includes a first step of applying the precursor film-forming composition according to claim 1 onto a substrate made of a poorly adhesive resin to form a coating film on the substrate; a second step of drying the coating film to remove the solvent and form a precursor film containing the organometallic compound; and a third step of irradiating the precursor film with ultraviolet light to remove organic components from the precursor film and convert the precursor film into an inorganic metal film, and activating the surface of the substrate by the catalytic activity of the components in the inorganic metal film to form an active surface on the surface of the substrate.

[0033] "First step" In the first step, the method for applying the precursor film-forming composition onto the substrate (application method) may be a general method capable of surface application, such as spin coating, bar coating, die coating, etc. By this application method, a coating film made of the precursor film-forming composition can be formed on the substrate.

[0034] "Second step" In the second step, the coating film formed on the substrate is dried at a temperature of 25° C. to 150° C. to remove the solvent and form a precursor film containing the organometallic compound. The coating film can be dried using a hot plate, an electric furnace, lamp heating, or other means.

[0035] "The third step" In the third step, the precursor film is irradiated with ultraviolet light to remove organic components from the precursor film, and the precursor film is converted into an inorganic metal film. At the same time, the surface of the substrate is activated by the catalytic activity of the components in the inorganic metal film, forming an active surface on the surface of the substrate.

[0036] When the precursor film-forming composition contains a transition metal ion compound, the precursor film and the inorganic metal film have particularly high absorbance to ultraviolet light (10 4 cm -1 ~10 5 cm -1 In this case, the concentration of the precursor film-forming composition is adjusted to make the inorganic metal film have a thickness of several nm to several tens of nm, and at least 1% or more of the amount of irradiated ultraviolet light reaches the resin surface.

[0037] When irradiated with ultraviolet light, the precursor film becomes an inorganic metal film (metal oxide film or metal film), and at the same time, it adheres strongly to the activated surface of the activated substrate, thereby coating the surface of the substrate made of a poorly adhesive resin with an easily adhesive inorganic material. The light source used for light irradiation may be either an ultraviolet laser or an ultraviolet lamp, but it is preferable to use ultraviolet lasers with less heating effect such as excimer lasers such as XeF (351 nm), XeCl (308 nm), KrF (248 nm), ArF (193 nm), and F2 (157 nm), as well as YAG lasers (fourth harmonic: 266 nm) and Ar ion lasers (second harmonic: 257 nm).

[0038] In surface treatments that use plasma treatment or the like to impart functional groups to the resin surface, the functional groups are exposed and therefore are easily changed in the atmosphere, and the treatment effect tends to have a short life span. In the method for producing a composite of this embodiment, the inorganic metal film that covers the surface of the substrate functions as a protective layer at the same time as the surface treatment of the substrate, so that the effect of the surface treatment can be sustained for a long period of time. In addition, by selecting an organometallic compound, it is also possible to simultaneously impart functions such as electrical conductivity to the surface of the substrate.

[0039] On the other hand, when the precursor film forming composition contains an alkali metal ion compound, the oxide or carbonate formed as the inorganic metal film can be removed by washing with water or a weak acid. Therefore, the surface of the surface-modified substrate can be exposed at an appropriate timing. In addition, the inorganic metal film can be removed from the surface of the substrate. In addition, since ultraviolet light is irradiated as a trigger for surface modification, the progress of the modification reaction can be easily controlled. Furthermore, compared with the case where a metallic sodium dispersion is used, the surface treatment of the substrate can be performed under milder conditions. Therefore, the surface of the substrate can be modified without causing discoloration or penetration of metal ions into the resin, which are problems in conventional methods.

[0040] According to the method for producing a composite of the present embodiment, the surface of the substrate is modified by a combination of applying a precursor film-forming composition to the surface of the substrate and irradiating the precursor film with ultraviolet light, so that the treatment area on the surface of the substrate can be easily controlled. In addition, according to the method for producing a composite of the present embodiment, a precursor film-forming composition that can be used stably and safely is used, so that the surface of the substrate can be modified locally only in the desired area by limiting the application area of ​​the precursor film-forming composition using various printing techniques or limiting the irradiation area of ​​ultraviolet light using a photomask or the like.

[0041] In the method for producing a composite of this embodiment, the shape of the substrate to be treated is not limited to a flat plate shape. The method for producing a composite of this embodiment can be applied to curved or uneven surfaces as long as the precursor film-forming composition can be applied and the ultraviolet light can be irradiated. In addition, since fluororesins generally have high transmittance to ultraviolet light, ultraviolet light can be irradiated through the resin as long as the transparency of the resin is high.

[0042] [Other embodiments] The present invention is not limited to the above embodiment. The composite and the method for producing the composite of the present invention may employ the following modified examples.

[0043] [Variations] Fig. 2 is a cross-sectional view showing a composite body according to one embodiment of the present invention. In Fig. 2, the same components as those in the above-mentioned embodiment are denoted by the same reference numerals, and their description will be omitted, and only the differences will be described. As shown in FIG. 2, a composite 10 of this embodiment has a substrate 2 made of a poorly adhesive resin, and an active surface 3 formed on a surface 2a of the substrate 2.

[0044] The arithmetic mean roughness (Ra value) of the surface 3a (3 μm square) of the active surface 3 is preferably 20 nm or less, more preferably 10 nm or less. If the arithmetic mean roughness (Ra value) of the surface (3 μm square) of the active surface 3 exceeds the upper limit, when used as a high-frequency communication circuit board of 100 GHz or more, the transmission loss caused by the unevenness of the surface 2a of the base material 2 increases, impairing the performance of the circuit.

[0045] The arithmetic mean roughness (Ra value) of the surface 3a (3 μm square) of the active surface 3 can be measured by a scanning method using a stylus or the like based on Japanese Industrial Standard JIS R 1683:2014.

[0046] According to the composite of the present embodiment, the active surface 3 formed on the surface 2a of the base material 2 is exposed, and therefore the surface 2a of the base material 2 has excellent adhesion even in applications where the inorganic metal film 4 is not desired.

[0047] [Method of manufacturing the composite] A method for producing a composite according to one embodiment of the present invention includes the first step in the above-described embodiment, the second step in the above-described embodiment, the third step in the above-described embodiment, and a fourth step of dissolving and removing the inorganic metal film with water or a weak acid to expose the active layer on the surface of the substrate.

[0048] "The fourth step" In the fourth step, the inorganic metal film is removed by washing with water or a weak acid. Weak acids include acetic acid, oxalic acid, and phosphoric acid.

[0049] According to the method for producing the composite of the present embodiment, the inorganic metal film is removed by washing with water or a weak acid, thereby exposing the active surface 3 formed on the surface 2a of the substrate 2, thereby improving the adhesion of the surface 2a of the substrate 2 in applications where the inorganic metal film 4 is not desired. EXAMPLES

[0050] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0051] Example 1 A mixed solution was prepared by dissolving 4.3 mg of Nikka Octytic Na 6% (manufactured by Nippon Chemical Industry Co., Ltd.) as an organometallic compound and 44 mg of Surflon S-611 (manufactured by AGC Chemical Co., Ltd.) as a surfactant in 10 mL of toluene as a solvent, and the mixed solution was stirred with a shaker to obtain a composition for forming a precursor film. The obtained precursor film-forming composition was dropped onto the surface of a perfluoroalkoxy fluororesin (PFA) substrate (manufactured by AS ONE Corporation) using a micropipette and then coated with a spin coater (3000 rpm, 10 s) to form a coating film. Next, the coating film was dried by heating on a hot plate at 100° C. for 10 minutes to remove the solvent contained in the coating film, thereby forming a precursor film. Next, the precursor film was irradiated with 248 nm ultraviolet light at 60 mJ / cm 2The surface of the substrate was irradiated with 2500 pulses to form an inorganic metal film and an active surface on the surface of the substrate. After the inorganic metal film was dissolved and removed with water, elemental analysis was performed by X-ray photoelectron spectroscopy, which will be described later.

[0052] Example 2 A mixed solution was prepared by dissolving 5 mL of NiO coating material SYM-NI05 (manufactured by Kojundo Chemical Co., Ltd.) as an organometallic compound and 44 mg of Surflon-611 (manufactured by AGC Chemical Co., Ltd.) as a surfactant in 5 mL of toluene as a solvent, and the mixed solution was stirred with a shaker to obtain a composition for forming a precursor film. Thereafter, in the same manner as in Example 1, an inorganic metal film and an active surface were formed on the surface of a substrate using the precursor film-forming composition of Example 2. After the surface of the inorganic metal film was washed with water and toluene, elemental analysis was performed by X-ray photoelectron spectroscopy, which will be described later.

[0053] Comparative Example 1 The substrate made of fluororesin was used as it was without surface treatment after washing the resin surface with water and toluene.

[0054] Comparative Example 2 A fluororesin substrate is exposed to ultraviolet light with a wavelength of 248 nm at 60 mJ / cm 2 The surface was irradiated with 2500 pulses.

[0055] [Elemental analysis by X-ray photoelectron spectroscopy] Elemental analysis was performed by X-ray photoelectron spectroscopy (XPS) using Al-Kα as a radiation source on the substrates of Examples 1 and 2 and Comparative Examples 1 and 2. The results are shown in FIGS. From the results of the carbon (C) 1s signal shown in Fig. 3, the peak intensity ratio between the peak (peak binding energy 292 to 294 eV) derived from the carbon-fluorine (CF) bond and the peak (peak binding energy 285 to 288 eV) derived from the carbon-oxygen (CO) bond is shown in Table 1. It was found that the number of CF bonds on the PFA resin surface was reduced by the surface treatment of the present invention and was replaced by CO bonds. The results of the oxygen (O) 1s signal shown in FIG. 4 indicate that the oxygen signal, which is hardly observed in Comparative Example 1 and Comparative Example 2, appears clearly in Examples 1 and 2. Furthermore, the results of the fluorine (F) 1s signal shown in FIG. 5 indicate that the fluorine signal in Examples 1 and 2 is weaker than that in Comparative Example 1 and Comparative Example 2. This also indicates that the C-F bonds on the surface of the substrate are replaced with C-O bonds.

[0056] [Table 1]

[0057] 6 shows the sodium (Na) Auger (KLL) signal in Example 1. It can be seen that no signal derived from sodium appears on the surface of the substrate, and the inorganic metal film made of a sodium compound is removed by washing with water. 7 shows the nickel (Ni) 2p signal in Example 2. A peak derived from nickel appears, indicating that an inorganic metal film made of a nickel compound was formed.

[0058] [Surface roughness measurement] Atomic force microscope images (3 μm×3 μm) were measured in accordance with Japanese Industrial Standard JIS R 1683:2014 to measure the arithmetic mean roughness (Ra) of the substrates of Examples 1 and 2 and Comparative Examples 1 and 2. The results are shown in Table 2.

[0059] [Table 2]

[0060] From the results shown in Table 1, it was found that the substrates of Examples 1 and 2 after surface treatment had surfaces as smooth as the untreated substrates of Comparative Examples 1 and 2. It was found that both the active surface exposed by removing the inorganic metal film in Example 1 and the inorganic metal film surface formed on the substrate surface via the active surface in Example 2 maintained the same smoothness as the substrate.

[0061] [Adhesive strength measurement] A 90-degree peel test was carried out in accordance with the Japanese Industrial Standard JIS K 6854-1 to measure the adhesive strength of various adhesives to the substrate of Example 2 and the substrates of Comparative Examples 1 and 2. A synthetic rubber adhesive (ThreeBond 1521 manufactured by ThreeBond Fine Chemical Co., Ltd.) and a silicone adhesive (Scotch Super Multi-Purpose 2 Ultra-Strong Adhesive manufactured by 3M Japan Ltd.) were used as the adhesive. The treated surface of the substrate and the polyimide resin were bonded with the adhesive, and the adhesive strength was measured after 6 hours or more had elapsed. The width of the measurement sample was 5 mm. Table 2 shows the adhesive strength with the synthetic rubber adhesive, and Table 3 shows the adhesive strength with the silicone adhesive.

[0062] [Table 3]

[0063] [Table 4]

[0064] From the results shown in Tables 2 and 3, it was found that the substrate of Example 2 after surface treatment had a significantly increased peel strength compared to the untreated substrates of Comparative Examples 1 and 2. This indicates that in addition to the formed inorganic metal film exhibiting good adhesion to the adhesive, the poorly adhesive PFA substrate and the inorganic metal film are strongly bonded via the activated surface with a bonding strength of 7 N / mm or more. [Explanation of symbols]

[0065] 1, 10 Complex 2 Base material 3 Active layer 4 Inorganic metal film

Claims

1. A precursor film-forming composition comprising an organometallic compound, a surfactant, and a solvent.

2. The precursor film-forming composition according to claim 1 , wherein the organometallic compound is a metal organic acid salt or a metal alkoxide.

3. The precursor film-forming composition according to claim 2 , wherein the organometallic compound is a compound that exhibits absorption of ultraviolet light having a wavelength of 100 nm or more and 400 nm or less.

4. 3. The precursor film forming composition according to claim 2, wherein the organometallic compound contains, as a metal ion, one or more metal elements selected from the group consisting of first transition metal elements Sc, Ti, V, Cr, Mn, Fe, Co, Ni, and Cu, and group 1 elements Li, Na, and K.

5. The precursor film forming composition according to claim 1 , wherein the surfactant is added in order to apply the solution of the precursor film forming composition to a poorly adhesive resin.

6. The precursor film-forming composition according to claim 1 , wherein the solvent is capable of dissolving the organometallic compound and the surfactant.

7. A substrate made of a poorly adhesive resin and an active surface formed on a surface of the substrate, The active surface has a carbon-fluorine (C—F) bond of the base material partially substituted with a carbon-oxygen (C—O) bond; A composite, in which a ratio of the content of the carbon-oxygen (C-O) bonds to the total amount of the carbon-fluorine (C-F) bonds and the carbon-oxygen (C-O) bonds (C-O bonds / (C-F bonds+C-O bonds)×100(%)) is 30% or more.

8. The composite according to claim 7, wherein the active surface has an arithmetic mean roughness (Ra value) of 20 nm or less on a surface (3 μm square).

9. An inorganic metal film is formed on the substrate via the active surface, The composite of claim 7 , wherein the inorganic metal film comprises a metal ion compound derived from an organometallic compound.

10. The composite according to claim 9 , wherein the inorganic metal film is bonded to the substrate via the active surface with a bonding strength of 7 N / mm or more.

11. The composite according to claim 9, wherein the inorganic metal film has a surface (3 μm square) having an arithmetic mean roughness (Ra value) of 20 nm or less.

12. The composite according to claim 7 , wherein the poorly adhesive resin is a fluororesin.

13. A first step of applying the precursor film-forming composition according to claim 1 onto a substrate made of a poorly adhesive resin to form a coating film on the substrate; a second step of drying the coating to remove the solvent and form a precursor film containing the organometallic compound; and a third step of irradiating the surface of the precursor film with ultraviolet light to remove organic components from the precursor film and convert the precursor film into an inorganic metal film, and activating a surface of the base material by catalytic activity of a component in the inorganic metal film to form an active surface on the surface of the base material.

14. The method for producing a composite according to claim 13, further comprising a fourth step of removing the inorganic metal film by dissolving it with water or a weak acid to expose the active surface on the surface of the substrate.

Citation Information

Patent Citations

  • Manufacture of laminated material of fluororesin methacrylic resin or acryl resin

    JP1995164600A

  • Surface treatment method for fluororesin and method of producing printed circuit board obtained by using fluororesin

    JP2003201571A

  • Production method of surface-modified molded body, and production method of composite body using the surface-modified molded body

    JP2016056363A